2017
DOI: 10.3164/jcbn.16-70
|View full text |Cite
|
Sign up to set email alerts
|

Chemical tools for detecting Fe ions

Abstract: Owing to its distinctive electrochemical properties with interconvertible multiple oxidation states, iron plays a significant role in various physiologically important functions such as respiration, oxygen transport, energy production, and enzymatic reactions. This redox activity can also potentially produce cellular damage and death, and numerous diseases are related to iron overload resulting from the dysfunction of the iron regulatory system. In this case, “free iron” or “labile iron,” which refers to iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 63 publications
2
55
0
1
Order By: Relevance
“…The former can be detected using inductively coupled plasma-MS or calcein AM quenching, as well as other specific iron probes (Hirayama and Nagasawa, 2017; Spangler et al, 2016), while the latter can be detected using phosphatidylcholine hydroperoxide reduction in cell lysates using LC-MS (Yang et al, 2014). …”
Section: Commonly Used Reagents For Studying Ferroptosismentioning
confidence: 99%
“…The former can be detected using inductively coupled plasma-MS or calcein AM quenching, as well as other specific iron probes (Hirayama and Nagasawa, 2017; Spangler et al, 2016), while the latter can be detected using phosphatidylcholine hydroperoxide reduction in cell lysates using LC-MS (Yang et al, 2014). …”
Section: Commonly Used Reagents For Studying Ferroptosismentioning
confidence: 99%
“…Recently, several redox state-selective fluorescent probes for Fe 2+ with a turn-on readout have been developed. 30 RhoNox-1, reported by our group, is the first example of detection of labile iron in live cells with a turn-on response, where N-oxide acts as a selective fluorogenic switch to Fe 2+ . 31 Subsequently, Chang et al reported IP-1 on the basis of a chelation-assisted oxidative C–O bond cleavage, which was successfully applied to detection of biologically stimulated accumulation of labile iron.…”
Section: Introductionmentioning
confidence: 95%
“…It has crucial roles in oxygen uptake, oxygen metabolism, electron transfer, and transcriptional regulation and a possible disorder in Fe ion metabolism cause several diseases (5,6). Thus, detection of Fe ions is useful in a wide range of area, including clinical diagnostics, therapeutic monitoring, and detection of organisms and toxins (7). Numerous research studies have been devoted on the development of Fe 2+ and/or Fe 3+ chemosensors (8).…”
Section: Introductionmentioning
confidence: 99%